Morphological Feature of the Ice Sheet in Mizuho Plateau - Shimizu, H.; Yoshimura, A.; Naruse, R.; Yokoyama, K. (1978)
P(論文) The morphological feature of the ice sheet in Mizuho Plateau, East Antarctica, was described by the use of data of elevation and maximum slope of the surface and thickness of the ice sheet obtained by oversnow traverses of the Japanese Antarctic Research Expeditions. A surface topographical map of Mizuho Plateau was also given. The upper boundary of the katabatic wind region was estimated at about 3100m from the distribution of the gradient of the ice sheet surface by applying BALL's theory (1960) to the data. The mean thickness of the ice sheet in Mizuho Plateau was 1650m, while the maximum was 3870m. Local trends of the bedrock surface were observed using cross-sectional profiles of the ice sheet. Mizuho Plateau was divided into subdivisional drainage basins of the ice sheet. It was estimated that the Shirase drainage basin, the largest one in this province, had an extent of 20×(10)^4(km)^2 in area, and stored ice amounting to 32×(10)^<13>t in weight. departmental bulletin paper